If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + -5) + (4x + 29) = 26 Reorder the terms: (-5 + 9x) + (4x + 29) = 26 Remove parenthesis around (-5 + 9x) -5 + 9x + (4x + 29) = 26 Reorder the terms: -5 + 9x + (29 + 4x) = 26 Remove parenthesis around (29 + 4x) -5 + 9x + 29 + 4x = 26 Reorder the terms: -5 + 29 + 9x + 4x = 26 Combine like terms: -5 + 29 = 24 24 + 9x + 4x = 26 Combine like terms: 9x + 4x = 13x 24 + 13x = 26 Solving 24 + 13x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 13x = 26 + -24 Combine like terms: 24 + -24 = 0 0 + 13x = 26 + -24 13x = 26 + -24 Combine like terms: 26 + -24 = 2 13x = 2 Divide each side by '13'. x = 0.1538461538 Simplifying x = 0.1538461538
| 15n-65=130 | | 3x-10y=-11 | | Ntimes-5=-155 | | -8m^3(3m^2)=0 | | 1/2log13.28 | | 7(3+4x)=-203 | | 3+2k=15 | | X+x-21=87 | | 2.35e^2x=947 | | 22-8/-2 | | f(1)=2x-1 | | 5[3(x+4)-2(1-x)]-x-15=14x+75 | | 1/2=-3/5y-2/3 | | (7x+11)+(16x-38)=77 | | -3+.5c=12 | | F(X)=-(x-1)*2+4 | | 5c+22=-11-10c+15c | | (24x-2)+(25x-8)=118 | | 3n^2+6n+18=0 | | 49m^2-36/25=0 | | 49m^2-36/25= | | 5x-2y=-50 | | 13+.25a=-3 | | m+11=20 | | 8x+6x=10 | | 4x-14*3=x+7*3 | | 2m-7=8-3 | | (7x+26)+(10x-25)=138 | | 15/x=90/7 | | .14x+26=.71x-22 | | 4w+1w+3w-7= | | 15/x=7/90 |